2018
DOI: 10.21714/2179-8834/2018v23n2p1-22
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Risk and Trust in the Bank's Brand on the Mobile Banking User Vision

Abstract: This research investigated the relationship between perceived risk by bank customers in the use of Mobile Banking (MB) and their trust in the bank's brand. The descriptive research was applied with 356 Brazilian customers that access their banking account via smartphones or tablets. Data analysis was performed using: descriptive and nonparametric statistics. The results show: the correlation between perceived risk in using the MB and the trust in the bank's brand; the influence of perceived risk in the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Perceive risk refers to clients' expectations of the occurrence of potential loss when performing online banking transactions (Lin et al, 2020;Razak, Hamid, Azhari, & Sonari, 2021;Solarz & Adamek, 2021). Additionally the influence of perceived risk dimensions including privacy, security, performance, time, financial, social and psychological risks have gained considerable empirical support in the previous literature studies (Almutairi, 2021;Amin, Ashraf, Nisar, & Hassan, 2021;Gelenske, Farias, & Santos Jr, 2018;Karim & Gide, 2019;Krishnan & Sheeja, 2020;Marriott & Williams, 2018;Reepu & Arora, 2022;Roy, Balaji, Kesharwani, & Sekhon, 2017). The results of these studies revealed that perceived risk dimensions have a negative influence on clients' usage of internet banking.…”
Section: Introductionmentioning
confidence: 99%
“…Perceive risk refers to clients' expectations of the occurrence of potential loss when performing online banking transactions (Lin et al, 2020;Razak, Hamid, Azhari, & Sonari, 2021;Solarz & Adamek, 2021). Additionally the influence of perceived risk dimensions including privacy, security, performance, time, financial, social and psychological risks have gained considerable empirical support in the previous literature studies (Almutairi, 2021;Amin, Ashraf, Nisar, & Hassan, 2021;Gelenske, Farias, & Santos Jr, 2018;Karim & Gide, 2019;Krishnan & Sheeja, 2020;Marriott & Williams, 2018;Reepu & Arora, 2022;Roy, Balaji, Kesharwani, & Sekhon, 2017). The results of these studies revealed that perceived risk dimensions have a negative influence on clients' usage of internet banking.…”
Section: Introductionmentioning
confidence: 99%